Determination of LC50 of permethrin acaricide in semi-engorged females of the tick Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Roma, Gislaine Cristina [UNESP]; de Oliveira, Patricia Rosa [UNESP]; Pizano, Marcos Aparecido [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
Currently, the most efficient and widely used method of tick control still is the treatment with acaricides, especially permethrin (active ingredient of the Advantage (R) Max3, Bayer), a pyrethroid with neurotoxic action. Due to the wide use of this acaricide in the control of the tick Rhipicephalus sanguineus, this study carried out laboratorial procedures to determine the LC50 (lethal concentration fifty) of permethrin in semi-engorged females of R. sanguineus. Based on the result of 14 dilutions of permethrin in distilled water and later Probit analysis, the LC50 of permethrin for R. sanguineus was 2062 ppm (1549-2675 ppm). This work can be used as a protocol with other chemicals, to determinate the LC50, basic procedure for studies of control, resistance and behavior of ticks treated with acaricides, especially the brown dog tick R. sanguineus. Also, the knowledge of the LC50 provides information on the potency of chemicals, the sensitivity of Arthropods to them and even estimates on pest control. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Ticks; Adult immersion test; Permethrin; Acaricides